MELAWAN NORMALISME DENGAN TEOLOGI PUBLIK DISABILITAS RM. JANSSEN, CM DALAM PERSPEKTIF MULTIKULTURAL - Rafael Aglis Ariya Tamtama (Pastoralia, 2026)
The "normalism" mindset, which assumes everyone must fit one standard, has marginalized people with disabilities in Indonesia. Public facilities and societal attitudes often only favor the majority. This research examines the ideas of Rm. Paulus Janssen, CM, regarding "public disability theology." It aims to see how his ideas can be used as a foundation to challenge this normalism, especially in Indonesia's diverse (multicultural) society. The method is qualitative library research, reviewing existing texts through a multicultural lens. The results show that Janssen's theology, demonstrated through the real-life practice of "living together," is a direct critique of normalism. This practice rejects the view of people with disabilities as mere objects of pity. Instead, Janssen affirms their equal dignity. From a multicultural perspective, this approach values bodily diversity as a richness, not a deviation from the standard. In conclusion, Janssen's disability theology is not just a spiritual reflection. It is a liberating social movement pushing Indonesia to become a more open, just, and humane society for all.